SPIRAL CYCLE MICRO-HYDRO COMMUNITY SYSTEM MODEL FOR SUSTAINABLE DEVELOPMENT IN YOGYAKARTA, INDONESIA - Alatas, Masrur; Budiastuti, Maria T. S.; Gunawan, Totok; Setyono, Prabang (Universiti Malaysia Terengganu, 2022)
Indonesia is committed to innovating and making breakthroughs in microhydro energy development. However, the problem is the lack of multi-stakeholder roles, especially local communities in its development, causing the poor operation of microhydropower plants. This research aims to apply the Spiral Cycle Micro-hydro Community System (SCMCS) Model through an eight-stage cycle process for the development of the Kedungrong micro-hydro power plant (MHPP) in Yogyakarta. The methods used are a qualitative approach, collecting data in the form of field observations, in-depth interviews and forum group discussion. The results and new findings indicate that SCMCS requires at least four cycles to be useful and sustainable. First is enhancing institutional, social and environmental aspects. Second is enhancing the technical aspects. Third involves improving the economic aspects. Fourth is optimizing the use of micro-hydro energy for micro-small enterprises. This model has successfully developed and preserved the MHPP project through integrated multi-stakeholder community participation in rural areas © Penerbit UMT